O que fizeram (e o que fizemos) de nós?: estudo de caso das trajetórias escolares de alunos/as do Ciclo Básico de Alfabetizaçã (CBA) em Minas Gerais - Frederico Assis Cardoso (2013)
This research, a case study type ex post facto, sought to understand and to problematize the implications that the schooling process had to the school trajectories of ex-students of the curriculum Ciclo Básico de Alfabetização (CBA), state schools of Minas Gerais (MG, Brazil) in the first class of students that was implemented, in Escola Estadual Barão de Macaúbas in Belo Horizonte/MG. The study sought to understand and analyze the differences and similarities of the school trajectories of these ex-students, comprising: 1) The determinants school itself, the school as an institution objectified, setting socialization and the curriculum of CBA as an pedagogical organizing principle, symptom and expression of a time; 2) The determinants of an action not-school, based cultural heritage pertaining to the arrangements and family configurations. The research made use of concepts such as: curriculum, individual, individual heritage of dispositions and school trajectories. The issues and research problems were analyzed from an approach that involved the contributions of both the dispositionalist sociology of education as of critical curriculum theories. In this research context, were adopted a qualitative methodological procedures prioritizing the use of data collection instruments such as questionnaires and interviews that favored the creation of the sociological profile configuration. Between 2010 and 2012 eight ex-students were located and interviewed (four men and for women) and also three ex-managers of the CBA: the Secretary of State for Education of Minas Gerais in 1985, the Director of the Escola Estadual Barão de Macaúbas and the teacher of students.